Coexistence of neuroblastoma detected on staging of Langerhans cell histiocytosis. Issue 4 (August 2014) - Shiohama, Tadashi; Ochiai, Hidemasa; Hishiki, Tomoro; Yoshida, Hideo; Kohno, Yoichi
Abstract Langerhans cell histiocytosis (LCH) is a rare proliferative disease accompanied by the accumulation of pathological Langerhans cells, which often spreads into multi‐site and multi‐organ systems. We here describe a girl with a history of Kawasaki disease and cervical lymphadenopathy who presented with occipital LCH. Adrenal tumor was detected on staging evaluation of LCH and was diagnosed as neuroblastoma on resection using laparoscopic surgery. Neither tumor relapsed following chemotherapy for LCH and resection of neuroblastoma. Although LCH often spreads into multi‐organ lesions, invasive biopsy may be needed for tumors with atypical localization for LCH in consideration of the synchronous occurrence of malignancies.